Nodal Global Efficiency in Front-Parietal Lobe Mediated Periventricular White Matter Hyperintensity (PWMH)-Related Cognitive Impairment - Chen, Haifeng; Huang, Lili; Yang, Dan; Ye, Qing; Guo, Mengdi; Qin, Ruomeng; Luo, Caimei; Li, Mengchun; Ye, Lei; Zhang, Bing; Xu, Yun (Frontiers in Aging Neuroscience, 2019)
White matter hyperintensity(WMH) is widely observed in the elderly population and serves as a key indicator of cognitive impairment(CI). However, the underlying mechanism remains to be elucidated. Herein, we investigated the topological patterns of resting state functional networks in WMH subjects and the relationship between the topological measures and CI. A graph theory-based analysis was employed in the resting-state functional magnetic resonance scans of 112 subjects (38 WMH subjects with cognitive impairment without dementia (CIND)，36 WMH subjects with normal cognition and 38 healthy controls(HCs), and we found that WMH with CIND subjects displayed decreased global efficiency at the levels of the whole brain, specific subnetworks (fronto-parietal network(FPN) and cingulo-opercular network(CON)) and certain nodes located in the FPN and CON, as well as decreased local efficiency in subnetworks. Our results demonstrated that nodal global efficiency in frontal and parietal regions mediated the impairment of information processing speed related to periventricular WMH(PWMH). Additionally, we performed support vector machine(SVM) analysis and found that altered functional efficiency can identify WMH-CIND subjects with high accuracy, sensitivity and specificity. These findings suggest impaired functional networks in WMH- CIND individuals and that decreased functional efficiency may be a feature of CI in WMH subjects.